2021
DOI: 10.1111/aos.14909
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal large disc of blue‐stained lyophilized amniotic membrane to treat complex macular holes: a 1‐year follow‐up

Abstract: Purpose: To report the long-term outcomes of large diameter epiretinal lyophilized amniotic membranes (lAMs) in recurrent or persistent macular holes (MHs) with or without rhegmatogenous retinal detachment (RRD), in a prospective interventional case series. Methods: Ten eyes of 10 patients underwent pars plana vitrectomy for MH-associated RRD (n = 5) or persistent MH without RRD (n = 5), in a university Hospital. A 3 or 4 mm diameter disc of lAM, stained with 0.06% trypan blue, was inserted with a catheter thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…12 Then, Garcin et al described the use of large diameter epiretinal lyophilized hAM in a cohort of 10 patients with recurrent or persistent macular holes associated or not with retinal detachment, reporting satisfactory visual recovery at one year. 13 Moreover, Qiao et al reported an improvement in visual acuity in almost 90% of patients treated with an epiretinal hAM patch for MHRD in highly myopic patients following failed primary surgery. 14 Epiretinal implant of the hAM plug could be technically easier compared to subretinal implant and could present less possible intraoperative complications, such as plug dislocation within the subretinal space during the fluid-air exchange or during the subretinal fluid drainage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Then, Garcin et al described the use of large diameter epiretinal lyophilized hAM in a cohort of 10 patients with recurrent or persistent macular holes associated or not with retinal detachment, reporting satisfactory visual recovery at one year. 13 Moreover, Qiao et al reported an improvement in visual acuity in almost 90% of patients treated with an epiretinal hAM patch for MHRD in highly myopic patients following failed primary surgery. 14 Epiretinal implant of the hAM plug could be technically easier compared to subretinal implant and could present less possible intraoperative complications, such as plug dislocation within the subretinal space during the fluid-air exchange or during the subretinal fluid drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our opinion, crucial differences are relevant in the present surgical technique compared to the previous abovementioned studies of hAM epiretinal implants. 12,13,14 Creating a retinotomy could represent a substantial improvement. Instead of draining through the macular hole as performed by Moharram et al, indeed, a retinotomy allows the aspiration of the subretinal fluid in a less traumatic way, avoiding the risk of enlarging the macular hole or inadvertently touching the subfoveal RPE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent publications have noted the use of amniotic membrane transplant in conjunction with vitrectomy for the treatment of macular holes [69][70][71]. Studies in vivo and in vitro have shown that AM transplantation can promote the regeneration of retinal tissue when placed under the fovea [72][73][74].…”
Section: Macular Hole Closurementioning
confidence: 99%